2018
DOI: 10.3389/fphys.2018.00149
|View full text |Cite
|
Sign up to set email alerts
|

Cryptochrome Regulates Circadian Locomotor Rhythms in the Small Brown Planthopper Laodelphax striatellus (Fallén)

Abstract: Most living organisms have developed internal circadian clocks to anticipate the daily environmental changes. The circadian clocks are composed of several transcriptional-translational feedback loops, in which cryptochromes (CRYs) serve as critical elements. In insects, some CRYs act as photopigments to control circadian photoentrainment, while the others act as transcriptional regulators. We cloned and characterized two cryptochrome genes, the Drosophila-like (lscry1) and vertebrate-like (lscry2) genes, in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 57 publications
1
15
0
Order By: Relevance
“…However, since it is classified as a vestigial flavoprotein (Kutta et al ., 2017), and is unlikely to be the magnetoreceptor; Cry2 may work together with another chromophore (e.g., FAD in Drosophila‐like Cry1 ) in magnetoreception. Moreover, given that Cry2 is a core component of the circadian clock (Zhang et al ., 2017; Jiang et al ., 2018), which has been shown to be sensitive to changes in magnetic field intensity (Yoshii et al ., 2009; Fedele et al ., 2014a), the altered gene expression pattern of Cry2 observed in our study was more likely related to its role in circadian mechanisms.…”
Section: Resultsmentioning
confidence: 99%
“…However, since it is classified as a vestigial flavoprotein (Kutta et al ., 2017), and is unlikely to be the magnetoreceptor; Cry2 may work together with another chromophore (e.g., FAD in Drosophila‐like Cry1 ) in magnetoreception. Moreover, given that Cry2 is a core component of the circadian clock (Zhang et al ., 2017; Jiang et al ., 2018), which has been shown to be sensitive to changes in magnetic field intensity (Yoshii et al ., 2009; Fedele et al ., 2014a), the altered gene expression pattern of Cry2 observed in our study was more likely related to its role in circadian mechanisms.…”
Section: Resultsmentioning
confidence: 99%
“…However, since it is classified as a vestigial flavoprotein (Kutta et al, 2017), and is unlikely to be the magnetoreceptor, Cry2 may work together with another chromophore (e.g., FAD in Drosophila-like Cry1) in magnetoreception. Moreover, given that Cry2 is a core component of the circadian clock (Jiang et al, 2018;Zhang et al, 2017), which has been shown to be sensitive to changes in magnetic field intensity (Fedele et al, 2014;Yoshii et al, 2009), the altered gene expression pattern of Cry2 observed in our study was more likely related to its role in circadian mechanisms.…”
Section: Glucose Levels Of 5th Instar Nymphsmentioning
confidence: 53%
“…Interestingly, the peak of cry2 expression at dusk observed in parthenogenetic aphids of the YR2 and GR strains coincides in phase with the peak of expression of period and timeless for the same aphid morphs Cortés et al, 2010). A peak at the beginning of the night in the expression of cry2, in many cases in phase with peaks in the expression of per and tim genes, has also been reported in other insects (Bertossa et al, 2014;Gentile et al, 2009;Ingram et al, 2012;Jiang et al, 2018;Rubin et al, 2006;Ueda et al, 2018;Werckenthin et al, 2012;Xu et al, 2016) but rhythmic expression has not been found in some insects (Ikeno et al, 2008;Kotwica-Rolinska et al, 2017;L. Zhu et al, 2017).…”
Section: Cry2 Expressionmentioning
confidence: 71%